2009
DOI: 10.1007/s10482-009-9312-0
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial activities of components of the glandular secretions of leaf cutting ants of the genus Atta

Abstract: The secretions of the mandibular and metapleural glands of leaf cutting ants contain antimicrobial substances that protect the mutualistic fungal colony within the nest from attack by parasitic micro-organisms. The major constituents of these secretions (citral, 4-methyl-3-heptanol, 2-heptanone, 3-octanone, 4-methyl-2-heptanone, beta-citronellol, geraniol, phenylacetic, indolacetic, hexanoic and octanoic acids were tested against resistant strains of the human pathogens, Escherichia coli, Staphylococcus aureus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(27 citation statements)
references
References 39 publications
1
26
0
Order By: Relevance
“…M. anisopliae and M. acridum are predicted to contain four and two CYP504s, respectively. CYP504s are used by fungi to degrade phenylacetate [50], an antimicrobial compound found in plants and insects [51]. The subfamily CYP53 is also represented in the PHI database as it is responsible for detoxification of benzoate and its derivatives [52].…”
Section: Resultsmentioning
confidence: 99%
“…M. anisopliae and M. acridum are predicted to contain four and two CYP504s, respectively. CYP504s are used by fungi to degrade phenylacetate [50], an antimicrobial compound found in plants and insects [51]. The subfamily CYP53 is also represented in the PHI database as it is responsible for detoxification of benzoate and its derivatives [52].…”
Section: Resultsmentioning
confidence: 99%
“…Both CYP53 and CYP504 family members were found to be upregulated during cuticle infection by insect pathogenic fungi Metarhizium anisopliae (four genes) and M. acridum (two genes) [50]. It was suggested that in these insect pathogens these CYP families carry out detoxification of insect released phenylacetate [50,51]. …”
Section: Resultsmentioning
confidence: 99%
“…Citronellol substantially increased the specific biofilm formation of E. coli ATCC 33456, possibly by acting as a poly L-lysine like adhesive 6 , but it decreased the specific biofilm formation of P. aeruginosa and P. putida at equivalent concentration ranges 20 . Also, geranial, β-citronellol were found in Pelargonium graveolens oil, geraniol and citronellol exhibited strong activity against C. albicans 16 but the antimicrobial activity of geraniol was more higher than β-citronellol, particularly against C. albicans 7 .…”
Section: Discussionmentioning
confidence: 95%